Image Guidance-Based Target Volume Margin Expansion in IMRT of Head and Neck Cancer. (February 2016) - Srivastava, Shiv P.; Cheng, Chee-Wai; Das, Indra J.
This study quantifies the setup uncertainties to optimize the planning target volume (PTV) margin based on daily image guidance, its dosimetric impact, and radiobiological implication for intensity-modulated radiation therapy (IMRT) in head and neck cancer. Ten patients were retrospectively chosen who had been treated with IMRT and with daily image-guided radiation therapy (IGRT). The daily setup errors of the 10 patients from on-board imaging for the entire treatment were analyzed. Planning target volumes were generated by expanding the clinical target volumes (CTVs) with 0 to 10 mm margins. The IMRT plans with the same dose–volume constraints were created in an Eclipse treatment planning system. The effect of volume expansion was analyzed with biological indices such as tumor control probability, normal tissue complication probability (NTCP), and equivalent uniform dose. Analysis of 906 daily setup corrections using daily IGRT showed that 98% of the daily setups are within ±5 mm. The relative increase in PTV-CTV volume from 0 to 10 mm margins provides nearly 4-fold volume increase and is linearly related to monitor unit (MU). The increase in MU is about 5%/mm margin increase. The relative increase in NTCP of parotids from 5 to 10 mm margins is 3.2 ± 1.15. Increase in PTV margin increases extra tissue volume with a corresponding increase in MU for treatment and NTCP values. Even a small margin increase (eg, 1 mm) may result in increase of more than 20% in relative extra volume and 15% in NTCP value of organs at risk (OARs). With image guidance, the setup uncertainty could be achieved within ±5 mm for 98% of the treatments, and a margin <5 mm for PTV may seem desirable to reduce the extra tissue irradiated, but at the expense of a more demanding setup accuracy.